ONE-LUNG VENTILATION PATIENTS: CLINICAL CONTEXT OF ADMINISTRATION OF DIFFERENT DOSES OF DEXMEDETOMIDINE: Dexmedetomidine in Patients Receiving One-lung Ventilation - Jiang, Hui; Kang, Yu; Ge, Chunlin; Zhang, Zhengying; Xie, Yan (Journal of Medical Biochemistry, 2021)
Background: To investigate the effects of different doses of dexmedetomidine on inflammatory response, oxidative stress, cerebral tissue oxygen saturation (SctO2) and intrapulmonary shunt in patients undergoing one-lung ventilation (OLV). Methods: Sixty patients undergoing open pulmonary lobectomy in our hospital from January 2016 to December 2017 were enrolled and randomly divided into high-dose dexmedetomidine group (group D1, 1 μg/kg, n=20), low-dose dexmedetomidine group (group D2, 0.5 μg/kg, n=20) and control group (group C, n=20). Then, arterial blood and internal jugular venous blood were taken before anesthesia induction (T0) and at 15 min after two-lung ventilation (T1) and 5 min (T2) and 30 min (T3) after OLV for later use. Next, the changes in hemodynamic parameters [mean arterial pressure (MAP), heart rate (HR) and pulse oxygen saturation (SpO2)] of patients were observed in each group. Enzyme-linked immunosorbent assay (ELISA) was carried out to detect serum inflammatory factors such as interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) and oxidative stress indicators [superoxide dismutase (SOD) and malondialdehyde (MDA)]. The changes in SctO2, arterial partial pressure of oxygen (PaO2) and intrapulmonary shunt Qs/Qt were observed. Additionally, the changes in lung function indicators like lung dynamic compliance (Cdyn) and airway peak pressure (Ppeak) were determined. Results: There were no statistically significant differences in the MAP, HR and SpO2 among three groups at each observation time point (P>0.05). At T2 and T3, the levels of serum IL-6, TNF-α and IL-8 were obviously decreased in group D1 and D2 compared with those in group C (P<0.05), and the decreases in group D1 were overtly larger than those in group D2, and the decreases at T3 were markedly greater than those at T2 (P<0.05). In comparison with group C, group D1 and D2 had notably reduced levels of serum reactive oxygen species (ROS) and MDA (P<0.05) and remarkably increased SOD content (P<0.05) at T2 and T3, and the effects were markedly better in group D1 than those in group D2. Besides, they were significantly superior at T3 to those at T2 (P<0.05). The SctO2 in group D1 and D2 was evidently lowered at T2 and T3 compared with that at T0, and the decrease in group D1 was distinctly smaller than that in group D2 (P<0.05). The Qs/Qt was significantly lower in group D1 and D2 than that in group C at T2 and T3 (P<0.05), while the PaO2 content was notably raised (P<0.05), and the decrease and increase were significantly larger in group D1 than those in group D2, and they were obviously greater at T3 to those at T2 (P<0.05). At T0 and T1, no significant differences were detected in the Cdyn, Pplat and Ppeak among three groups. At T2 and T3, the Cdyn was significantly elevated, while the Pplat and Ppeak overtly declined (P<0.05), and group D1 had greater changes in comparison with group D2, and the changes were obviously more evident at T3 to those at T2 (P<0.05). Conclusions: Dexmedetomidine effectively ameliorates inflammatory response and oxidative stress, lowers oxygenation, Qs/Qt and the decrease in SctO2 and improves lung function during OLV, with good efficacy.